Tips for Surviving and Excelling in a Master and Doctoral Program Under the 40s With Honorable Recognitions - Ms. Monica Jaramillo (RGUHS Journal of Nursing Sciences)
There is an imminent need to assist advanced-practice nursing students in decreasing stress and pressure concerning graduate and postgraduate studies. This short manuscript seeks to inspire other students especially immigrants and minority individuals to pursue higher education degrees. The framework of this composition emerges from recent evidence suggesting not only the challenges that students undergo while completing their advanced degrees but also the importance of proper planning self-care support systems and perseverance to ensure success in all academic endeavors. In addition to the recent peer-reviewed literature concerning the many challenges advanced practice students experience while completing their academic degree this manuscript also contains real stories. These stories arise from a nursing student who survived and excelled in the educational journey and now seeks to inspire other students of all programs to believe in themselves. No doubt engaging in any academic program brings stress and challenges but positive practices and inspirational stories can empower all students to take control of their fears and have an enjoyable learning experience. It is time to support and motivate each other to achieve higher education while propelling all professions. Stories are powerful instruments to encourage others through role modeling and support. There is hope for all students experiencing significant challenges. It is a matter of accepting the inspiration of others and believing it is possible.